2021
DOI: 10.1038/s41392-021-00503-9
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Tumor microenvironment: an evil nexus promoting aggressive head and neck squamous cell carcinoma and avenue for targeted therapy

Abstract: A Correction to this paper has been published: https://doi.org/10.1038/s41392-021-00503-9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…HNSC is a common malignant tumor with a poor prognosis characterized by rapid growth and a high metastasis rate over the world [ 16 ]. Currently, although surgery is an effective treatment for locally advanced HNSC tumors, there are currently few options available for those that have disseminated; the clinical treatment of patients with metastatic HNSC remains a major clinical challenge because of heterogeneity [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…HNSC is a common malignant tumor with a poor prognosis characterized by rapid growth and a high metastasis rate over the world [ 16 ]. Currently, although surgery is an effective treatment for locally advanced HNSC tumors, there are currently few options available for those that have disseminated; the clinical treatment of patients with metastatic HNSC remains a major clinical challenge because of heterogeneity [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TME comprises of the extracellular matrix (ECM), basement membrane (BM), tumor-infiltrating immune cells, neuroendocrine cells, endothelial cells, adipose cells, cancer-associated fibroblasts (CAFs), pericytes, cancer stem cells (CSCs), cytokines, and a plethora of signaling molecules that modulate tumor progression ( Macha et al, 2020 ; Bhat et al, 2021a ; Bhat et al, 2021b ; Nisar et al, 2021b ; Mehraj et al, 2021 ; Neophytou et al, 2021 ; Bhat et al, 2022 ). The interactions between tumor cells and their microenvironment are very critical for cell survival, and therefore impact the development and growth of tumors ( Gajewski et al, 2013 ; Bhat et al, 2021a ; Bhat et al, 2021b ; Nisar et al, 2021b ; Bhat et al, 2022 ). It also plays a crucial role in cancer metastasis by providing the necessary support and signals for tumor survival, growth, and migration to new sites in the body.…”
Section: Lncrnas Modulate Tumor Microenvironment During Metastasismentioning
confidence: 99%
“…Increasing evidence indicated that the tumor microenvironment (TME), formed by noncancerous cells surrounding the tumor and extracellular matrix (ECM) proteins and enriched with chemokines, cytokines, and immune modulators that are secreted by both the tumor and stromal cells, played a critical role in HPV-related tumorigenesis and made them resistant to therapy [42][43][44][45]. For example, cytotoxic T cells and NK cells have been shown to have tumor inhibition abilities.…”
Section: Lessons Learned From Clinical Trialsmentioning
confidence: 99%